Pregnancy complications in last pregnancy and mothers' long-term cardiovascular mortality: does the relation differ from that of complications in first pregnancy? A population-based study - Abdu Kedir Seid; Nils-Halvdan Morken; Kari Klungsøyr; Liv Grimstvedt Kvalvik; Linn Marie Sorbye; Lars Johan Vatten; Rolv Skjærven (BMC, 2023)
Abstract Background Women who experience complications in first pregnancy are at increased risk of cardiovascular disease (CVD) later in life. Little corresponding knowledge is available for complications in later pregnancies. Therefore, we assessed complications (preeclampsia, preterm birth, and offspring small for gestational age) in first and last pregnancies and the risk of long-term maternal CVD death, taking women´s complete reproduction into account. Data and methods We linked data from the Medical Birth Registry of Norway to the national Cause of Death Registry. We followed women whose first birth took place during 1967-2013, from the date of their last birth until death, or December 31st 2020, whichever occurred first. We analysed risk of CVD death until 69 years of age according to any complications in last pregnancy. Using Cox regression analysis, we adjusted for maternal age at first birth and level of education. Results Women with any complications in their last or first pregnancy were at higher risk of CVD death than mothers with two-lifetime births and no pregnancy complications (reference). For example, the adjusted hazard ratio (aHR) for women with four births and any complications only in the last pregnancy was 2.85 (95% CI, 1.93-4.20). If a complication occurred in the first pregnancy only, the aHR was 1.74 (1.24-2.45). Corresponding hazard ratios for women with two births were 1.82 (CI, 1.59-2.08) and 1.41 (1.26-1.58), respectively. Conclusions The risk for CVD death was higher among mothers with complications only in their last pregnancy compared to women with no complications, and also higher compared to mothers with a complication only in their first pregnancy.